Comparison of Phonemic Fluency Test Results Using Different Letters among Persian Speakers - Najme Mardani; Ramin Mahdipour; Mohammad Hossein Rouhani; Kowsar Baghban (Shiraz University of Medical Sciences, 2017)
Background: The purpose of this study was to compare the results obtained from phonemic fluency test using "F"1 , "A"2 , "S"3 and "L"4 , "T"5 ,"M"6 among Persian Speakers aged between 20 and 30 years. Methods: In this applied study, 76 subjects were randomly chosen. The data was analyzed separately for each subject according to the three letters: "F", "A", and "S" by using the routine phonemic fluency subtest of verbal fluency test and then phonemic fluency performance was gathered by using the three letters: "L", "T" and "M" and after scoring according to Troyer method, the resultant numbers were reported after statistical analyses. For statistical analysis using SPSS 19, the distribution of data was firstly evaluated. Due to the fact that the data distribution was normal, Bonferroni test was used to compare the scores of the letters. Results: No significant gender and educational level effects were found and therefore, all further analyses were conducted without taking gender and educational level into account. Also, when the results of the three letters: "F", "A" and "S" as a group for phonemic fluency performance and "L", "T" and "M" letters as a different group, were integrated, a significant difference was found between the mean cluster size and switching between these two groups, while there was no significant difference between the average cluster size and cluster number. Conclusion: Based on the findings of this research, it can be concluded that the results of phonemic fluency test in each of the six letters are significantly different. Therefore, when using the special letters in the Persian language, it is necessary to examine all the letters for phonological sub-tests and use the simplest letters to study this function.